Pengembangan Media Pembelajaran Berbasis Web Menggunakan Wordwall pada Materi Bangun Ruang Sisi Lengkung - Feni Windiyan Sari; Fahrur Rozi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This study aims to develop web-based learning media using wordwall on the topic of curved-sided solid figures for Grade IX students at SMP Islam Al Fattahiyyah. The research was conducted in response to the limited use of interactive media and the low student motivation in mathematics learning, particularly in geometry. The development process follows the ADDIE model (Analyze, Design, Development, Implementation, and Evaluate). Validation by two media experts resulted in scores of 83% and 95% (very good), and the content expert gave a score of 82,2% (very good). Small group trials scored 74,77% and large group trials 81,29%, resulting in an overall average of 83%, which is categorized as “Highly Feasible”. The wordwall-based media enables enganging and interest in geometry, specifically in curved-sided solid figures.